2022
DOI: 10.1021/acsami.1c18647
|View full text |Cite
|
Sign up to set email alerts
|

Fully Room-Temperature Reprogrammable, Reprocessable, and Photomobile Soft Actuators from a High-Molecular-Weight Main-Chain Azobenzene Crystalline Poly(ester-amide)

Abstract: Azobenzene (azo) polymer photoactuators with full room-temperature reprogrammability, reprocessability, and photomobility are highly desirable for large-scale applications, but their development remains a daunting challenge. Herein, a strategy is first presented for fabricating such advanced photoactuators from a highmolecular-weight main-chain azo crystalline poly(ester-amide) (PEA) prepared via Michael addition polymerization. This azo PEA can be readily processed into both physically cross-linked, uniaxiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 49 publications
3
39
0
Order By: Relevance
“…In this context, it is worth mentioning that there should also exist crystalline domain-induced physical cross-linking networks in these unaxially oriented samples, as described in our previous report. 25 However, the above results indicated that they hardly made any contribution to the photomechanical effects of the studied fibers and films. It is also noteworthy here that although the UV light-induced disruption of H-bonding 68 and crystallinity 53 has been reported to be responsible for the photomobile behaviors of some main-chain azo polymers, the photoinduced azo switching proved to have negligible influence on the H-bonding and crystallinity of our photodeformable samples under the studied photoirradiation conditions (Fig.…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…In this context, it is worth mentioning that there should also exist crystalline domain-induced physical cross-linking networks in these unaxially oriented samples, as described in our previous report. 25 However, the above results indicated that they hardly made any contribution to the photomechanical effects of the studied fibers and films. It is also noteworthy here that although the UV light-induced disruption of H-bonding 68 and crystallinity 53 has been reported to be responsible for the photomobile behaviors of some main-chain azo polymers, the photoinduced azo switching proved to have negligible influence on the H-bonding and crystallinity of our photodeformable samples under the studied photoirradiation conditions (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…, PEA- n -3 h or briefly PEA- n ). 25 These Michael addition polymerization systems remained homogeneous throughout the whole polymerization processes. Orange-yellow azo PEAs were obtained in high yields (90–92%, entries 1, 4 and 7 in Table 1) after the reaction mixtures were precipitated into MeOH and thoroughly washed with MeOH until no M-EA- n was detected by thin layer chromatography.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations